Comparison of Remimazolam and Propofol for Intravenous Anesthesia on Trigeminocardiac Reflex in Percutaneous Balloon Compression for Trigeminal Neuralgia: A Randomized Controlled Trial - Long D; Chen K; Li Y; He P; Li X; Qin X; Wang Y; Xiao Y (Dove Medical Press, 2024)
DongJu Long,1 Kai Chen,1 YaXi Li,1 PeiYao He,1 XinNing Li,1,2 XiuNan Qin,1 YaPing Wang,1,2 YanYing Xiao1,2 1Department of Anesthesiology and Pain Management, The Second Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China; 2Department of Pain Management, Clinical Research Center for Pain Medicine in Hunan Province, Changsha, Hunan, People's Republic of ChinaCorrespondence: YanYing Xiao, Department of Anesthesiology and Pain Management, The Second Xiangya Hospital, Central South University, Changsha, Hunan, People's Republic of China, Tel +86-13467609491, Fax +86-731-85292115, Email xiaoyanying192@csu.edu.cnBackground: Trigeminal neuralgia usually presents as incapacitating facial pain. Percutaneous balloon compression (PBC) is frequently utilized to manage this ailment. Trigeminocardiac reflex (TCR) commonly presents with sudden severe bradycardia or even asystole, alongside a sudden increase in blood pressure during this surgical procedure. Notably, remimazolam has been reported to maintain higher heart rate (HR) levels during anesthesia than propofol. Thus, this study aims to assess the impact of remimazolam anesthesia versus propofol on TCR occurrence during this procedure.Methods: This randomized controlled trial involved patients with trigeminal neuralgia scheduled for elective PBC. Patients were randomly assigned to receive either remimazolam or propofol for anesthesia. The primary outcome was the incidence of TCR, a potential complication during the procedure. Secondary outcomes included the occurrence of severe TCR, usage of atropine, HR at the time of foramen ovale puncture (T4), HR at the time of trigeminal ganglion compression (T5), and any adverse events.Results: A total of 80 patients were included in the study, with 40 patients in each group. The incidence of TCR was significantly lower in the remimazolam group compared to the propofol group (30.0% vs 82.5%; risk difference − 52.5%, 95% CI − 67.3% to − 18.6%; P < 0.001). The remimazolam group also showed a lower incidence of severe TCR (7.5% vs 45.0%) and significantly lower usage of atropine compared to the propofol group (P < 0.001). Furthermore, HR at T4 and T5 were higher in the remimazolam than in the propofol group (P < 0.001). There was no significant difference in the incidence of adverse events between the two groups.Conclusion: In PBC surgery for trigeminal neuralgia, remimazolam-based intravenous anesthesia showed a higher HR and a lower incidence of TCR than propofol without any increased adverse events.Keywords: remimazolam, propofol, trigeminal neuralgia, balloon occlusion, methods, reflex, trigeminocardiac, hemodynamics